2019
DOI: 10.7759/cureus.3812
|View full text |Cite|
|
Sign up to set email alerts
|

Epiligament Tissue of the Medial Collateral Ligament in Rat Knee Joint: Ultrastructural Study

Abstract: Introduction Recent studies stressed the importance of the epiligament in ligament nutrition and healing. While ligaments of the knee joint have been the subject of extensive research, the epiligament of the medial collateral ligament has received only limited attention. The aim of our study was to present the ultrastructural morphological features of the epiligament of the medial collateral ligament in a rat knee joint. Materials and methods For the present study, we used eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Similar ultrastructural characteristics of fibroblasts and fibrocytes, as reported above, were confirmed by Georgiev et al [ 8 ] in humans. They finally concluded due to the ultrastructural characteristics that fibroblasts might be involved in differentiation, phagocytosis, and collagen synthesis; the authors also hypothesized that single collagen fibers or those grouped in bundles may respond to ligament tension in different directions [ 8 , 21 ]. With the aim of obtaining more detailed knowledge of the MCL and ACL ELs and comparing it in rats, Iliev et al [ 32 ] found a statistically significant difference in the number of cells per mm 2 in the EL of the two ligaments, with a greater number in the MCL.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar ultrastructural characteristics of fibroblasts and fibrocytes, as reported above, were confirmed by Georgiev et al [ 8 ] in humans. They finally concluded due to the ultrastructural characteristics that fibroblasts might be involved in differentiation, phagocytosis, and collagen synthesis; the authors also hypothesized that single collagen fibers or those grouped in bundles may respond to ligament tension in different directions [ 8 , 21 ]. With the aim of obtaining more detailed knowledge of the MCL and ACL ELs and comparing it in rats, Iliev et al [ 32 ] found a statistically significant difference in the number of cells per mm 2 in the EL of the two ligaments, with a greater number in the MCL.…”
Section: Introductionmentioning
confidence: 99%
“…After extensive research on epiligament morphology of the MCL in rats and humans in both normal conditions and injury, as well as investigation of the same tissue in the ACL and comparison between these two commonly injured ligaments, a novel EL theory was proposed by Georgiev et al [6–8, 11, 12, 18–22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations